2018
DOI: 10.1063/1.5043295
|View full text |Cite
|
Sign up to set email alerts
|

Dual-pulse laser ignition model

Abstract: A two-dimensional mathematical model of dual-pulse laser ignition that self-consistently integrates Navier-Stokes, translational and vibrational energy, and neutral and charged species equations has been presented. The results showed that the ignition kernel dynamics depends on the shape and initial energy distribution in the energy spot created by the first ultraviolet laser pulse. The results also suggest that the ignition delay time and the flame kernel development depend on the laser intensity, vibrational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 27 publications
0
34
0
1
Order By: Relevance
“…The proposed study will also include the influence of vibrational and electronic energy transfer mechanisms during the nonequilibrium energy deposition and thermalization process during the equilibrium energy deposition (e.g. Spark) [7]. The electron-induced reaction rates, electron species transport parameters, mobility and diffusivity, and the electron energy mobility and diffusivity and the ions and neutrals can be treated hydrodynamically in a CFD code.…”
Section: Randd Methods and Anticipated Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed study will also include the influence of vibrational and electronic energy transfer mechanisms during the nonequilibrium energy deposition and thermalization process during the equilibrium energy deposition (e.g. Spark) [7]. The electron-induced reaction rates, electron species transport parameters, mobility and diffusivity, and the electron energy mobility and diffusivity and the ions and neutrals can be treated hydrodynamically in a CFD code.…”
Section: Randd Methods and Anticipated Resultsmentioning
confidence: 99%
“…The initial results suggested that the electron, vibrational, and gas temperatures quickly (~100 ns) reach a steady-state condition, which can not be captured by conventional modeling approaches. Besides, the time at which the electron temperature reaches a steady state is related to plasma lifetime and strongly relies on energy deposition rate [7]. However, the initial calculations suggested that the vibrational-translational energy exchange mechanism is much slower than the electronic-translational and electronic-vibrational process.…”
Section: Randd Methods and Anticipated Resultsmentioning
confidence: 99%
“…The ability to control the energy deposition can be especially valuable in gas flow control problems. In addition, this approach turned out to be in demand for plasma-stimulated ignition and combustion [86,89].…”
Section: Pulsed Nanosecond Optical Dischargesmentioning
confidence: 99%
“…Возможность конроля за вкладываемой энергией может оказаться особенно ценной в задачах управления потоками газа. Кроме того, этот подход оказался востребованным и для стимулированного плазмой воспламенения и горения[86,89].…”
unclassified
“…A computational fluid dynamics (CFD) analysis has shown the role of plasma-driven gas dynamics to enhance the early kernel growth, in particular an ability to tailor the resulting laser plasma (by adjusting the axial offset of the two laser pulses) to either suppress or admit the typical 3rd lobe feature which in turn is linked to the ability to ignite lean mixtures 16 . Kinetic modeling has examined nonequilibrium and electron dynamics in the dual-pulse preionization laser plasmas 17 .…”
Section: Introductionmentioning
confidence: 99%